The impact of network competition in the mobile industry - George Houpis; Jose Maria Rodriguez; Thomas Ovington; Goran Serdarevic (International Telecommunications Society (ITS), 2015)
In 2000, there were as many countries served by a single mobile network as by network competition. Today, only 30 countries, representing less than 3% of the world's population, are served by a single network. There has been considerable discussion about the optimal number of network operators in the mobile industry. More recently, some regulators and governments have considered implementing a single wholesale network to deliver next generation mobile services due to concerns around low coverage, inefficient duplication of costs and lack of competition. To date, the authors are not aware of such single wholesale networks fully implemented in mobile industry. What is clear is that single wholesale networks represent a U-turn with respect the way in which the mobile industry has developed worldwide. Therefore, it is important to carefully examine the available evidence on the performance of mobile markets in countries with a single mobile networks, as this is could shed some light on the expected performance of single wholesale networks. The key result is that countries with network competition have higher coverage, higher take-up and greater innovation than countries with a single mobile network, controlling for other relevant factors. This paper represents a significant contribution to the literature, as the authors are not aware of any other papers that have considered the impact of network competition compared to single networks on outcomes such as coverage. The results of the paper have significant policy implications, as they imply that moving away from the network competition model into the world of single wholesale networks could cause considerable consumer harm, which may be difficult to reverse once there has been a move away from network competition.
Keywords: 330; regulation; single mobile network; competition; mobile telecommunications